Assessing causality between obstructive sleep apnea with the dyslipidemia and osteoporosis: a Mendelian randomization study - Hong, Ping-Yang; Liu, Dong; Liu, Ang; Su, Xin; Zhang, Xiao-Bin; Zeng, Yi-Ming (Frontiers in Genetics, 2024)
This study aims to assess the causal relationship between Obstructive Sleep Apnea (OSA), dyslipidemia, and osteoporosis using Mendelian Randomization (MR) techniques.Methods: Utilizing a two-sample MR approach, the study examines the causal relationship between dyslipidemia and osteoporosis. Multivariable MR analyses were used to test the independence of the causal association of dyslipidemia with OSA.Single nucleotide polymorphisms (SNPs) were selected as instrumental variables based on genome-wide significance, independence, and linkage disequilibrium criteria. The data were sourced from publicly available Genome-Wide Association Studies (GWAS) of OSA(n=375,657) from the FinnGen Consortium, the Global Lipids Genetics Consortium of dyslipidemia(n=188,577) and the UK Biobank for osteoporosis (n=456,348).The MR analysis identified a significant positive association between genetically predicted OSA and triglyceride levels (OR: 1.15, 95% CI: 1.04-1.26, p = 0.006) and a negative correlation with high-density lipoprotein cholesterol (HDL-C) (OR: 0.84, 95% CI: 0.77-0.93, p = 0.0003). Conversely, no causal relationship was found between dyslipidemia (total cholesterol, triglycerides, HDL-C, and low-density lipoprotein cholesterol) and OSA or the relationship between OSA and osteoporosis.The study provides evidence of a causal relationship between OSA and dyslipidemia, highlighting the need for targeted prevention and management strategies for OSA to address lipid abnormalities. The absence of a causal link with osteoporosis and in the reverse direction emphasizes the need for further research in this area.